MODERN APPROACHES AND PRINCIPLES IN DEFINING THE GRAMMATICAL MINIMUM - Madina Akhmadjanova (Western European Studies, 2025)
this article analyzes modern approaches and fundamental principles for defining the grammatical minimum. The grammatical minimum serves to simplify the teaching process by identifying and highlighting the most essential rules in language instruction. The author explores linguistic, psychological, and didactic foundations while evaluating the significance of functional, competence-based, and reflective approaches. The competence-based approach aims to develop learners' communicative and grammatical competencies, whereas the functional approach emphasizes the practical significance of grammatical structures in real-life contexts. Additionally, the article examines the role of the principles of minimalism, relevance, and progression from simplicity to complexity in defining the grammatical minimum. According to the minimalism principle, only the most necessary grammatical rules are selected, while the relevance principle focuses on choosing materials that align with learners' needs. The corpus linguistics-based approach enables the study of language materials through authentic communication. The author provides recommendations on implementing the grammatical minimum in the educational process and suggests strategies for enhancing teaching effectiveness.
Keywords: grammatical minimum; language education; linguistic approach